Utilization of Generative Artificial Intelligence Technologies as Learning Tools among University Students : A Cross-Sectional Study - Md Mizanur, Rahman; Chai, Chau Chung; Angellisa, Shanana; Sthanny Ajang, Sim Chu Hua; Thiviyashree, Pathmanathan; Elleyajasmin, Ahmad (Kassel University Press GmbH., 2025)
ABSTRACT Artificial intelligence (AI) technologies have the potential to revolutionize the higher-education landscape by offering personalized and adaptive learning experiences. This study aimed to investigate the utilization of AI technologies as a learning tool among university students and identify the factors influencing it. This study utilized a cross-sectional design and collected data through a self-administered questionnaire developed based on the technology acceptance model and Theory of Planned Behavior (TPB). Data from 581 respondents were analyzed using SPSS version 29, employing descriptive statistics and multivariate hierarchical multiple linear regression analysis. The study found that AI technologies were widely utilized by students for various academic tasks, with clarifying understanding (76.1%), paraphrasing (71.6%), and academic translations (71%) being the most common. ChatGPT (91.4%), QuillBot (82.8%), and Grammarly (79.7%) emerged as the most popular AI tools among the participants. A hierarchica1l multiple regression analysis revealed that motivation (β = .17, p = .002), subjective norms (β = .14, p < .001), and intention to use (β = .49, p < .001) were significant predictors of AI technology use among students. This study highlights the widespread adoption of AI technologies for academic tasks among university students. Higher education institutions foster an environment that enhances students’ motivation, addresses subjective norms, and cultivates a positive intention towards AI technology adoption to facilitate its effective integ ration into the learning process.